Prognostic Implications of the Complement Protein C1q in Gliomas - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Zacchi, Paola; Iacopino, Domenico Gerardo; Martorana, Anna; Rodolico, Vito; Bonazza, Deborah; Zanconati, Fabrizio; Kishore, Uday; Bulla, Roberta (Frontiers in Immunology, 2019)
The contribution of the complement system in the pathophysiology of brain cancers has been recently considered in light of its well-known involvement in carcinogenesis. Complement system represents an important component of the inflammatory response and acts as a functional bridge between the innate and adaptive immune response. C1q, the first recognition subcomponent of the complement classical pathway, has recently been shown to be involved in a range of pathophysiological functions that are not dependent on complement activation. C1q is expressed in the microenvironment of various types of human tumours, including melanoma, prostate, mesothelioma and ovarian cancers, where it can exert a protective or a harmful effect on the cancer progression. In view of the local synthesis of C1q in the central nervous system, the involvement of C1q in glioma pathogenesis has been poorly investigated. We, therefore, decided to perform a bioinformatics analysis, using Oncomine dataset and UALCAN database analysis, in order to assess whether C1q could serve as a potential prognostic marker for gliomas. Our bioinformatics analysis, coupled with immunohistochemistry and fluorescence microscopy, appears to suggest a positive correlation between C1q expression and unfavourable prognosis only in gliomas grade-II and -III, while no clear correlation was observed in glioblastoma multiforme.